2003
DOI: 10.1079/bjn2002754
|View full text |Cite
|
Sign up to set email alerts
|

Food sources of nutrients in the diet of Spanish children: the Four Provinces Study

Abstract: The aim of the present study was to assess the principal food sources of energy and nutrients among Spanish children. We used a cross-sectional study design, based on results obtained from a food-frequency questionnaire. The sample included 1112 children, aged 6-7 years, from Cadiz, Madrid, Orense and Murcia, Spain. Children were selected through random clustersampling in schools. We analysed the percentage contributed by each food item to total energy and nutrient intake. The most important food sources were:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
4
31
0
1
Order By: Relevance
“…Similarly to our study, milk was the main calcium source in another survey among Spanish children, (26% in Spain compared with 50% in Belgium) (Royo-Bordonada et al, 2003). Fish was the main vitamin D source in Spanish children (43%), while margarine/butter in Flemish preschoolers (9% in Spanish children) (Royo-Bordonada et al, 2003).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly to our study, milk was the main calcium source in another survey among Spanish children, (26% in Spain compared with 50% in Belgium) (Royo-Bordonada et al, 2003). Fish was the main vitamin D source in Spanish children (43%), while margarine/butter in Flemish preschoolers (9% in Spanish children) (Royo-Bordonada et al, 2003).…”
Section: Resultssupporting
confidence: 85%
“…Fish was the main vitamin D source in Spanish children (43%), while margarine/butter in Flemish preschoolers (9% in Spanish children) (Royo-Bordonada et al, 2003). Comparison with main vitamin D contributors among 4-year-old Swedish children showed that in the Swedish preschoolers, the contribution of margarine, butter and oils (20%) and of fish (11%) to total vitamin D intakes was lower in comparison with our Flemish preschoolers (Garemo et al, 2007).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…However, a progressive shift to a non-Mediterranean pattern, even in countries bordering the Mediterranean Sea, has been observed (44) . Previous studies carried out in Spain confirmed that young generations (5)(6)(7)(8)(9)(10)(11) are further away from the Mediterranean dietary pattern. Lately, we found that the average adherence to the Mediterranean dietary pattern in our adolescent population was 58 % (11) .…”
Section: Discussionmentioning
confidence: 76%
“…Recent nutritional surveys carried out in Spain also confirmed a progressive departure from the traditional Mediterranean diet towards a Western dietary pattern, mainly in young generations (5)(6)(7)(8)(9)(10)(11) . Because there is evidence that nutritional behaviours track from adolescence into adulthood, the promotion of healthy nutrition during adolescence has the potential to confer significant long-term health benefits (1) .…”
mentioning
confidence: 86%